PENGARUH PRODUCT INNOVATION DAN BRAND IMAGE TERHADAP PURCHASE INTENTION (STUDI PADA KONSUMEN PRODUK SCARLETT WHITENING) - Annisa Aurelia Eksananda; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
One of the industrial sectors currently multiplying in Indonesia is the skincare industry. Brand competition and skincare product innovation attract the attention of consumers to buy skincare products. This study aims to determine the effect of product innovation and brand image on the purchase intention of Scarlett Whitening products. This type of research uses quantitative methods. The population in this study were respondents who knew about the Scarlett Whitening product with a total sample of 120 respondents, using a non-probability sampling technique. The method used was judgmental sampling, distributed using an online questionnaire. Data analysis used the multiple linear regression method with the help of the SPSS program version 26. The results showed that product innovation and brand image had a positive and significant effect on the purchase intention of Scarlett Whitening products. The theoretical implication of this research is that product innovation and brand image affect purchase intention with a very strong (positive) and proportional relationship. Meanwhile, the significance of this research on the cosmetic and skincare industry is expected to be a reference in business management by optimizing the development of product variations and brand utilization.